Turning ideas into actions! How research on identity, psychological resources, and leadership support can Inform career coaching. Issue 2 (3rd July 2019) - Vucic, Marija; Bolton, Lucy E.
ABSTRACT: The aim of this paper is to contribute new insights to the Career Coaching field, based on findings drawn from empirical research on career transition. The paper examines the relationship between future work self and proactive career behaviours in an employed, multinational sample considering or experiencing a career transition. It evaluates whether psychological resources for career transition and perceived supervisory support positively moderate this relationship. A quantitative survey design was implemented and data analysed through linear regression analyses. The findings confirm that individuals with a clearer idea of their future work self reported higher levels of proactive behaviours. Moreover, participants with greater psychological resources for career transition and supervisory support in career development found it easier to translate their future work self vision into specific career-oriented behaviours. The paper provides recommendations on how Career Coaching practitioners can utilise these findings when devising interventions to facilitate a career transition process.